2021
DOI: 10.1039/d1ra01648b
|View full text |Cite
|
Sign up to set email alerts
|

Prominent roles of Ni(OH)2 deposited on ZnIn2S4 microspheres in efficient charge separation and photocatalytic H2 evolution

Abstract: The capture of the photogenerated holes by the deposited Ni(OH)2 contributes to the efficient charge separation, allowing more photogenerated electrons to be left on ZnIn2S4 to reduce H+ to H2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Another pair of peaks located at 861.48 and 880.08 eV is in accordance with two shakeup satellite ones for Ni 2p 3/2 and Ni 2p 1/2 . These binding energies of Ni 2p match well the characteristics of Ni 2+ in Ni­(OH) 2 according to previous reports. , Furthermore, as shown in Figure S5a–5c, the deposition of Ni­(OH) 2 on Cd 1– x Mn x S ( x = 0.5) gives a slight shift in the binding energies of Cd 3d, Mn 2p, and S 2p in Cd 1– x Mn x S ( x = 0.5). The observed shifts support a strong interaction between the Ni­(OH) 2 and Cd 1– x Mn x S ( x = 0.5), which would benefits the charge transfer between them.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Another pair of peaks located at 861.48 and 880.08 eV is in accordance with two shakeup satellite ones for Ni 2p 3/2 and Ni 2p 1/2 . These binding energies of Ni 2p match well the characteristics of Ni 2+ in Ni­(OH) 2 according to previous reports. , Furthermore, as shown in Figure S5a–5c, the deposition of Ni­(OH) 2 on Cd 1– x Mn x S ( x = 0.5) gives a slight shift in the binding energies of Cd 3d, Mn 2p, and S 2p in Cd 1– x Mn x S ( x = 0.5). The observed shifts support a strong interaction between the Ni­(OH) 2 and Cd 1– x Mn x S ( x = 0.5), which would benefits the charge transfer between them.…”
Section: Resultssupporting
confidence: 90%
“…After the deposition of 5% Ni­(OH) 2 on the Cd 1– x Mn x S ( x = 0.5) sample, as observed in the HRTEM image of 5% Ni­(OH) 2 /Cd 1– x Mn x S ( x = 0.5) composite (Figure c), the nanoparticles with an interplanar spacing of 0.27 nm appears on the surface of the major phase CdS-hosted Cd 1– x Mn x S in Cd 1– x Mn x S ( x = 0.5). The interplanar spacing of 0.27 nm well corresponds to the interplanar distance for the crystallographic plane (100) of hexagonal Ni­(OH) 2 . , Moreover, the presence and homogeneous distribution of various elements in the selected area of these samples are also well demonstrated by the EDS mapping images (Figure S3).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…34,36,41 Another consensus suggests that Ni(OH) 2 plays the prominent role of capturing photogenerated holes from the semiconductor, boosting charge transfer. 38 Based on these hypotheses, it is expected that the construction of Ni(OH) 2 –ZIS heterostructures may aid efficient photocatalytic FA oxidation coupled with H 2 production in water, while such an ensemble has not been achieved to date. Moreover, it is essential to get deeper insights into the issues regarding photogenerated charge capture and separation, as well as active sites, in the Ni(OH) 2 –semiconductor composites applied as catalysts for coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…18,[30][31][32][33] Among them, Ni(OH) 2 , which features the merit of facile deposition, has attracted extensive attention. Specifically, Ni(OH) 2modified typical semiconductor materials, including Ni(OH) 2 / CdS nanorods, 34,35 Ni(OH) 2 /TiO 2 nanotubes, 36 Ni(OH) 2 /g-C 3 N 4 , 37 Ni(OH) 2 /ZIS nanoflowers 38,39 and Ni(OH) 2 /CdS/reduced graphene oxide ternary composite, 40 have been reported as costeffective photocatalysts for water splitting to produce H 2 . As for alcohol oxidation application, Liu et al reported the selective oxidation of benzyl alcohol using a Ni(OH) 2 -modified CdS-MoS 2 composite with significantly enhanced activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%